Motywy zwierzęce w Apokalipsie św. Jana - Korabik, Kamila (Motywy fauny i flory w literaturze i kulturze, 2018)
This article is a discussion on the symbolism of the animals that appear in the Apocalypse of St. John, and of the part they play. Motives of the Satan and the lamb have been analyzed in special way. There is also a reference to how the particular species of the animals of the Apocalypse evolved throughout the pages of the Old Testament. The reference is supported by properly chosen citations.